Adaptation of patients diagnosed with human papillomavirus: a grounded theory study - Narjes Nick; Camellia Torabizadeh; Mehdi Ghahartars; Roksana Janghorban (BMC, 2021)
Plain language summary Human papillomavirus (HPV) is the most common cause of sexually transmitted diseases. Almost all men and women get the infection at least once throughout their lives. The high-risk types of HPV account for about 5% of cancer cases globally. HPV can cause anogenital cancers and warts in both genders. In this grounded theory study, we conducted 27 in-depth interviews with Iranian patients, their spouses, and health care providers from April 2019 to December 2020. The collected data were analyzed using Corbin and Strauss's method (2015) and MAXQDA 2018. The participants were concerned about tension in family relationships, being stigmatized, getting cancer, recurrence of warts, transferring their disease to others, and changes in the appearance of their genitalia. They stated that HPV is regarded as a shameful disease in society. Most of the participants said they had never heard anything about HPV. The patients' action/interaction responses to their concerns were "emotional confrontation" and "maintaining resilience." These strategies helped the patients recover some of their tranquility. However, some of patients' concerns were persistent and kept them oscillating between tension and tranquility. An understanding of the patients' perception of their disease is essential to development of effective educational interventions to change patients' perspective on their situation and improve their recovery. Furthermore, because of the low level of public awareness about HPV and sexual health and the flow of misinformation to the infected, it is recommended that educational interventions focus on the patients' concerns.